HUBUNGAN SIKAP DENGAN PARTISIPASI IBU DALAM MEMBAWA BAYINYA UNTUK IMUNISASI DPT - Sylvina Rahmawati; Nova Purmahardini; Emdat Suprayitno (Sekolah Tinggi Ilmu Kesehatan Estu Utomo Boyolali, 2022)
Background: DPT immunization is given to infants for active immunity at the same time against diphtheria disease. The success of DPT immunization in infants is the attitude and participation of mothers in bringing their babies for immunization. Research objective: To determine the relationship between attitudes and mothers' participation in bringing their baby to DPT immunization at the Palengaan Health Center, Pamekasan Regency. Research design: This type of research is a cross-sectional study conducted from April 24 to June 30, 2021. With total sampling, the population is 37 mothers whose babies are 0-2 months old. Data were collected using a questionnaire and analyzed by statistical test chi-square test. The results of the study: Mothers who had a positive attitude towards DPT immunization, respondents immunized DPT to their babies (100%). mothers with negative attitudes immunize DPT their babies (100%). with a significance level of = 0.000 which means <? (? = 0.05). Conclusion: there is a relationship between a mother's attitude towards DPT immunization and with mother's participation in bringing her baby for DPT immunization at the Palengaan Health Center, Pamekasan Regency, in 2021. Keywords: attitude, DPT immunization, participation, mothers who have babies aged 0-2 months